The Influence Of The Quality Of Financial Reports Of The UMKM As well as prospects For The Implementation of SAK ETAP - Teti Rahmiati Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is to test the influence of financial statements of UMKM on the level of credit received UMKM, as well as the prospects of the implementation of SAK Entities Without Public Accountability (SAK ETAP) in 2011 to increase the quality of financial statements of UMKM. The Data in this study were obtained from the questionnaire with the respondent UMKM entrepreneurs residing in the territory of Surabaya, Gresik, and several other areas on the island of Java. Respondents were 50 of the sample in this study. The results of this study shows that the quality of financial reports of UMKM tidakberpengaruh to the amount of the credit received UMKM, this is due to the low quality of the financial statements of UMKM so that the banks still doubt the relevance and reliability of the quality of its financial reports. The prospect of the implementation of SAK ETAP to improving the quality of financial statements to the extent this is still facing constraints due to the still low level of understanding of the SME entrepreneurs over the SAK ETAP such